Performance analysis and optimization biogas-fuelled cogeneration systems in sewage treatment plants - Mohamad Firdaus, Basrawi (2012)
In terms of securing energy resources and reducing environmental problems, the utilization of biomass has been studied. Biomass is known as renewable energy which can supply more stable energy than other renewable energy types such as wind and solar energy. Thus, its application has become more important in the recent years. Abundant biogas has been produced by anaerobic digestion of sewage sludge, one of waste type biomass in sewage treatment plants. Thus, its utilization potential is very high. The installation of efficeint power plant systems in sewage treatment plants is indispensable for the efficient utilization of biogas. In this study, micro gas turbines (MGTs) were used as the prime movers of Cogeneration Systems (CGS5). MGTs have low emissions and maintenance requirements and can also use fuel with low heating value. The performance and the optimized configuration method of the system was investigated in this study.In the initial stage, the effect of ambient temperature on the basic component of the biogas-fuelled CGS, the energy balance of the anaerobic digestion and performance of the MGT-CGS was clarified. On the basis of this result, improvement of the performance of the biogas-fuelled CGS in a cold region that has high and varies heat demand throughout the year was investigated. In this case, the CGS alone cannot cover the total heat demand and hence other auxiliary equipment including a boiler, a heat pump and a gas storage system were also considered. It was found that performance can be improved when the boiler was replaced by the heat pump, and all biogas produced and exhaust heat recovered by the CGS can be efficiently used when the gas storage system was also installed with the CGS. In the second stage, focused was given to the optimized configuration method of the CGS that can utilize all biogas produced efficiently regardless of the region and ambient temperature conditions. It was clarified that in terms of energy utilization efficiency, the most efficient CGS can be obtained when the exhaust heat index of the CGS, exhaust heat recovery efficiency , e/1r is approximately equal to the energy index of the plant, ratio of annual average of heat demand Qhto the biogas energy produced Qb.p, (Qh.d I Qb.p)On the other hand, MGTs are classified as gas turbines that have electrical power output capacity of 30-300kW, and depending on the output capacity, their electrical power output efficiency at full load and partial load are different. Thus, in the third stage, the suitable size (electrical power output capacity) of an MGT-CGS depending on the scale of the sewage treatment plant (biogas energy produced) and its optimization was investigated. It was found that the most efficient MGT-CGS can be obtained when the fuel energy input of the MGT-CGS at full load is approximately equal to the biogas energy produced of the plant. Finally, it can be summarized that this study successfully clarifies in detail the most efficient configuration of cogeneratiofls based biogas-fuelled power plants and, this study can also give valuable guide regarding the method of the performance optimization of a biogas-fuelled CGS.